1999
DOI: 10.1590/s1415-47571999000400023
|View full text |Cite
|
Sign up to set email alerts
|

Numerical chromosome polymorphism in Mikania cordifolia Willd. (Asteraceae)

Abstract: Cytogenetical analysis of Mikania cordifolia, from southeastern Brazil, using the conventional Feulgen method, showed a chromosome number of 2n = 36. Previous karyotypic descriptions for this species showed a numerical chromosome variation of 2n = 34 to 38. There was a secondary constriction in every metaphase in the first chromosome pair, which constitutes a cytological marker. Small extranumerary chromosomes with numerical variation in the same plant were found in the tenth chromosome pair.
As análises ci…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…In a study of ten species of Mikania Ruas (1989) and Ruas and Aguiar-Perecin (1997) proposed a correlation between morphological and chromosomal evolution, while an analysis of 12 cytotypes of Mikania micrantha by Maffei (1996) showed that the same evolutionary mechanisms that occur among species also occur at intraspecific level, results also seen in a study of two populations of M. cordifolia by Maffei et al (1999a).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…In a study of ten species of Mikania Ruas (1989) and Ruas and Aguiar-Perecin (1997) proposed a correlation between morphological and chromosomal evolution, while an analysis of 12 cytotypes of Mikania micrantha by Maffei (1996) showed that the same evolutionary mechanisms that occur among species also occur at intraspecific level, results also seen in a study of two populations of M. cordifolia by Maffei et al (1999a).…”
Section: Introductionmentioning
confidence: 89%
“…Chromosome studies show a regular aneuploid series with x = 17, 18, 19, 20 and 21 in the genus Mikania (King et al, 1976;Robinson and King, 1977;King and Robinson, 1987;Ruas and Ruas, 1987;Ruas, 1989;Ruas and AguiarPerecin, 1997;Maffei et al, 1998Maffei et al, , 1999a, with aneuploidy seeming to be an important component of chromosomal evolution in this genus.…”
Section: Karyotype Evolutionmentioning
confidence: 95%
See 2 more Smart Citations
“…Este gênero possui aproximadamente 415 espécies (KING & ROBINSON, 1987) com distribuição tropical (MAFFEI et al, 1999). Está melhor representado na América do Sul, sendo amplamente distribuído no Brasil, onde aproximadamente 200 espécies têm sido descritas (RUAS & AGUIAR-PERECIN, 1997).…”
Section: Mikania)unclassified